Design, Synthesis, and Biological Evaluation of Vanillin Hydroxamic Acid Derivatives as Novel Peptide Deformylase Inhibitors - Gao, Jian; Qiu, Shengzhi; Liang, Li; Hao, Zhixiang; Zhou, Qianqian; Wang, Fanfan; Mou, Jie; Lin, Qisi (Current Computer - Aided Drug Design, 2018)
Background: Infectious disease is increasingly hampering human health, which challenge the discovery of new antibacterial target. Peptide deformylase (PDF), a metalloenzyme responsible for catalyzing the removal of the N-formyl group from nascent proteins, was considered as an important target in antibacterial drug discovery. Objective: Reported here are the design, synthesis and biological evaluation of vanillin hydroxamic acid derivatives. Methods and Results: Analysis of the structure-activity relationships lead to the discovery of compound 8, which exhibits promising antibacterial activity against Escherichia coli, Staphylococcus aureus, Aspergillus oryzae, and Aspergillus foetidus with the MIC value of 0.32 μg/ml, 0.32 μg/ml, 0.16 μg/ml and 0.16 μg/ml, respectively. Furthermore, molecular docking study was applied to elucidate binding interaction between compound 8 and PDF, which indicate that compound 8 not only shares the same binding pocket with actinonin, but also has a similar binding pattern. In silico pharmacokinetic and toxicity prediction studies also suggested that compound 8 has a relatively high drug score of 0.80, and has no risk of toxicity. Conclusion: Compound 8 might represent a promising scaffold for the further development of novel antibacterial drugs.
Keywords: Peptide deformylase